MANAGEMENT OF FUNDS OF THE STATE BUDGET AND LOCAL BUDGETS IN UKRAINE - SEMENOVA, Valentyna; TROPININA, Yelyzaveta (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the problems of managing the funds of the State budget and local budgets in Ukraine, since the effective management of budget funds becomes a key factor for ensuring the financial stability of the state and regions.The purpose of the study is a comprehensive analysis of the current state of management of funds of the State Budget and local budgets of Ukraine, identification of key problems and development of recommendations for improving the system of management of budget funds.The system of managing the funds of the State budget and local budgets in Ukraine was considered and conclusions were drawn about the presence of serious challenges, especially in the conditions of the ongoing martial law. Analysis of the structure of revenues and expenditures of the State Budget revealed significant changes due to the need to finance defense needs. In particular, there is a significant increase in the share of defense and security spending, which puts pressure on other budget items, such as the social sphere, education and health care. Local budgets, despite difficult economic conditions, show a tendency to increase revenues and expenditures, which indicates the effectiveness of the decentralization reform and the ability of local authorities to adapt to new challenges.Also, the study revealed a number of problematic aspects in the management of budget funds. In particular, the growth of the budget deficit and public debt creates risks for the country's long-term financial stability. There is a need to find an optimal balance between meeting current needs, especially in the field of defense, and maintaining funding for important socio-economic programs. The expediency of implementing a comprehensive approach to the management of budget funds is substantiated. This includes improving the system of strategic budget planning, strengthening mechanisms for controlling the use of funds, optimizing the structure of expenditures, and developing a long-term strategy for public debt management
Keywords: fund management; state budget; local budget; income and expenditure structure